Science literacy or value predisposition? A meta-analysis of factors predicting public perceptions of benefits, risks, and acceptance of nuclear energy - Ho, Shirley S. (2020)
Nuclear energy is widely regarded as a controversial technology that polarizes public opinion. Guided by the scientific literacy and cognitive miser models, this study systematically identified and examined the magnitude of the effects of 19 predictors on public perceptions of benefits, risks, and acceptance of nuclear energy. We meta-analysed 34 empirical studies, representing a total sample of 32,938 participants and 129 independent correlations. The findings demonstrated that trust substantially affected public perception of benefits regarding nuclear energy. Sex, education, public perception of benefits regarding nuclear energy, trust, and public deliberation substantially influenced public perception of risks regarding nuclear energy. Moreover, sex, education, public perceptions of benefits, risks and costs regarding nuclear energy, knowledge, and trust substantially affected public acceptance of nuclear energy. Country of sample and time period of data collection moderated public perceptions of benefits, risks, and acceptance of nuclear energy. Implications for future research are discussed.